Interrogation and torture integrating efficacy with law and morality - Gaggioli, Gloria; Fallon, Mark; Barela, Steven J. 1971- (Ethics, national security, and the rule of law, 2020)
This book focuses on the science, law and morality behind interrogational methods. It develops, for the first time, a comprehensive discussion regarding the legality of torture and the efficacy of interrogation. In other words, scientific research has concluded that torture is not effective. This then raises a natural question: What interrogational methods are effective? How does one employ those methods in way that is consistent with law and morality?"--